2012
DOI: 10.5209/rev_sjop.2012.v15.n2.38872
|View full text |Cite
|
Sign up to set email alerts
|

Morningness-Eveningness and Health-Related Quality of Life among Adolescents

Abstract: Accumulating evidence suggests that evening-type adolescents are exposed to a number of determinants that might have a negative impact on their health condition. Given that few studies have investigated the association between chronotype and quality of life measures in large samples of adolescents, the aim of this study was to assess the relationship between morningness-eveningness and health-related quality of life among 1600 adolescents (aged 12-16 years). Adolescents completed the Veçú et Santé Perçue de L'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…As shown in Table 1 and Supplementary Table 2, the psychometric properties of the MESC have been reported in studies based on American, Australian, Croatian, Dutch, Hong Kong-Chinese, Israeli, Italian, Spanish, Taiwanese and Turkish samples. Of the 25 studies that reported Cronbach's alpha values, five presented scores of ≥ 0.80 [23,24,27,49,83], fourteen studies reported values between 0.70 and 0.79 [3,17,18,20,21,25,26,31,38,42,43,48,51,78], while six showed values < 0.70 [8,16,28,29,40,46].…”
Section: Review Of Circadian Preference Measuresmentioning
confidence: 99%
“…As shown in Table 1 and Supplementary Table 2, the psychometric properties of the MESC have been reported in studies based on American, Australian, Croatian, Dutch, Hong Kong-Chinese, Israeli, Italian, Spanish, Taiwanese and Turkish samples. Of the 25 studies that reported Cronbach's alpha values, five presented scores of ≥ 0.80 [23,24,27,49,83], fourteen studies reported values between 0.70 and 0.79 [3,17,18,20,21,25,26,31,38,42,43,48,51,78], while six showed values < 0.70 [8,16,28,29,40,46].…”
Section: Review Of Circadian Preference Measuresmentioning
confidence: 99%
“…Preliminary evidence suggests that evening-type diurnal preference is associated with poor diet 21 and depression 22 and has adverse effects on measures of quality of life in adolescents. 23 We previously showed an association between evening type and habitual short and long sleep duration in a twin sample. 12 Since both short and long sleep are associated with adverse health outcomes, [24][25][26][27][28][29][30][31][32][33][34] these fi ndings suggest that the evening type may represent an endophenotype for poor health.…”
mentioning
confidence: 91%
“…In particular, morningness has been consistently shown to be related to more advantageous facets of well-being (Prieto et al 2012). Furthermore, eveningness has been linked to greater depressiveness both in healthy individuals (Hidalgo et al 2009;Levandovski et al 2011) and in clinical conditions (Ahn et al 2008;Hasler et al 2010).…”
Section: Introductionmentioning
confidence: 99%